2019
DOI: 10.26444/monz/104752
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of the medical staff on the recommended vaccinations against influenza

Abstract: Cel pracy. Główny Inspektorat Sanitarny, corocznie publikując Program Szczepień Ochronnych, włącza się w realizację międzynarodowych wytycznych dotyczących profilaktyki zachorowań na grypę, które zalecają, aby personel medyczny regularnie poddawał się szczepieniom. Celem pracy było poznanie opinii pracowników medycznych-lekarzy, pielęgniarek, położnych i ratowników medycznych-na temat zalecanych szczepień przeciwko grypie oraz określenie czynników wpływających na częstotliwość wykonywania szczepień (występują … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Similar results were obtained by Sternal and Owsianko, stating that 20.2% of their respondents performed irregular vaccinations, while 12.5% of the respondents had themselves vaccinated regularly every year [27]. Of particular concern is the fact that in Poland a small part of the nursing staff is vaccinated, and it is the nurse who is the person who has the most frequent contact with patients [16,27,28]. In the literature, the main reason for such a small group of workers undergoing vaccination is the lack of adequate knowledge about this type of flu prevention [14,28].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar results were obtained by Sternal and Owsianko, stating that 20.2% of their respondents performed irregular vaccinations, while 12.5% of the respondents had themselves vaccinated regularly every year [27]. Of particular concern is the fact that in Poland a small part of the nursing staff is vaccinated, and it is the nurse who is the person who has the most frequent contact with patients [16,27,28]. In the literature, the main reason for such a small group of workers undergoing vaccination is the lack of adequate knowledge about this type of flu prevention [14,28].…”
Section: Discussionsupporting
confidence: 87%
“…This is due to the fact that only every third respondent is in favour of vaccination, and in the current season (2018-2019) only 17.6% declared that they have been vaccinated, and only 13% are vaccinated annually. Similar results were obtained by Sternal and Owsianko, stating that 20.2% of their respondents performed irregular vaccinations, while 12.5% of the respondents had themselves vaccinated regularly every year [27]. Of particular concern is the fact that in Poland a small part of the nursing staff is vaccinated, and it is the nurse who is the person who has the most frequent contact with patients [16,27,28].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Research by Tomljenovic M. et al showed that in a group of 465 doctors and nurses, as many as 17% were identified as denying the effectiveness of protective vaccinations [ 54 ]. Sternal D. and Owsianko A., in a study of 105 hospital employees, showed that as many as 67.3% of them were not vaccinated against influenza, even though vaccination against influenza is recommended for healthcare professionals [ 55 ]. Paris C. et al studied almost 2,000 employees in the French health care system, and found that when the COVID-19 vaccine appeared, as many as 23% of them hesitated to take it and 4% refused [ 56 ].…”
Section: Discussionmentioning
confidence: 99%